Pengelolaan sampah rumah tangga berbasis motivasi RT. 03/03 kelurahan Meruyung Limo Depok - Sudrajat, Yayan; Wiyanti, Endang; Atmapratiwi, Heppy (PT. Lancar Media Komunikasi, 2022)
The purpose of this community service is to provide motivation-based socialization of household waste management to housewives in the Meruyung Village area, Limo Village, Depok. The method used is the lecture method combined with the lecture method plus questions and answers and assignments, the lecture method plus discussion and practice on how to manage motivation-based waste so that it becomes something useful. The target audience in the implementation of this activity is housewives in the neighborhood where abdimas partners are. The implications of this activity are (1) to be able to manage household waste into something useful; (2) enabling IRT (housewives to be creative and innovative towards goods that are no longer useful (garbage) so that they can be of sale value (3) can increase income especially in the post-pandemic period.